2002
DOI: 10.1111/j.1527-3466.2002.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptide Factor Xa Inhibitors: DPC423, a Highly Potent and Orally Bioavailable Pyrazole Antithrombotic Agent

Abstract: DPC423, 1‐[3‐(aminomethyl)phenyl]‐N‐[3‐fluoro‐2′‐(methylsulfonyl)[1,1′‐biphenyl]‐4‐yl]‐3‐(trifluoromethyl)‐1H‐pyrazole‐5‐carboxamide, is a synthetic, orally bioavailable, competitive, and selective inhibitor of human coagulation factor Xa (Ki [nM]: factor Xa, 0.15; trypsin, 60; thrombin, 6000; plasma kallikrein, 61; activated protein C, 1800; factor IXa, 2200; factor VIIa, >15,000; chymotrypsin, >17,000; urokinase, >19,000; plasmin, >35,000; tissue plasminogen activator, >45,000; complement factor I, 44,000 [I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Furthermore, rabbit models have been found to be suitable models for assessment of FXa inhibitors. This is because they are comparable to humans in terms of in vitro anticoagulation effect of FXa inhibitors [43], and are more sensitive to small molecule FXa inhibitors than mice, rats or dogs [44,45]. In addition, the use of a randomised design and of both placebo and negative control groups allowed for a rigorous evaluation of rivaroxaban reversal with 4F-PCC.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, rabbit models have been found to be suitable models for assessment of FXa inhibitors. This is because they are comparable to humans in terms of in vitro anticoagulation effect of FXa inhibitors [43], and are more sensitive to small molecule FXa inhibitors than mice, rats or dogs [44,45]. In addition, the use of a randomised design and of both placebo and negative control groups allowed for a rigorous evaluation of rivaroxaban reversal with 4F-PCC.…”
Section: Discussionmentioning
confidence: 96%
“…In general, rabbits are a more sensitive model to small molecule FXa inhibitors than mice, rats or dogs [8,28,29] and have therefore been widely used as thrombosis disease models (i.e., arteriovenous-shunt thrombosis, venous thrombosis and electrolytic-injured carotid arterial thrombosis) in studies looking at the antithrombotic efficacy of FXa inhibitors [8,28]. Furthermore, our study has also demonstrated that the rabbit model is comparable to humans in terms of in vitro anticoagulation effect of FXa inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, compound 65 was selected for clinical development. 141,142 In effort to further optimize the selectivity, various substitutions on P1 were explored based on 65. The search led to 66 (DPC 602; fXa K i 5 0.91 nM, fIIa K i 5 3,600 nM, trypsin K i 5 3,500 nM), which has an ortho-substituted methylamine instead of the meta-substitution found in 65.…”
Section: Synthetic Direct Fxa Inhibitorsmentioning
confidence: 99%